Programmed Death Ligand 1: A Poor Prognostic Marker in Endometrial Carcinoma - Mianxin Chew; Yin Ping Wong; Norain Karim; Muaatamarulain Mustangin; Nurwardah Alfian; Geok Chin Tan (Diagnostics, 2020)
Endometrial carcinoma is the only gynaecologic malignancy with a raising incidence and mortality, posing a major health concern worldwide. The upregulation of programmed death ligand 1 (PD-L1) on tumour cells causes T-cell suppression, which impedes antitumour immunity, promotes immune cell evasion and enhances tumour survival. The aim of this study was to evaluate PD-L1 expression in endometrial carcinoma and to correlate it with survival rate. A total of 59 cases of endometrial carcinoma were evaluated. Thirty-two cases of non-neoplastic endometrial tissue were included as control. PD-L1 immunohistochemistry was performed on all cases. PD-L1 expression was evaluated on tumour cells and immune cells. PD-L1 was positive in 62.7% (37/59) and 28.8% (17/59) of immune cells and tumour cells, respectively. PD-L1 expression in immune cells was significantly higher in endometrial carcinoma than in non-neoplastic endometrium (p < 0.001). Among the patients with endometrial carcinoma, PD-L1 expression in tumour cells was significantly higher in patients who died (10/15, 66.7%) compared to those who survived (7/44, 15.9%) (p < 0.001). It is noteworthy to point out that the expression of PD-L1 in tumour cells was significantly associated with a poor survival. This suggests that immunomodulation using PD-L1 inhibitors may be useful in advanced endometrial carcinoma.